Environmental Management in cities: A Perspective from the Akure Solid Waste Management Authority, Ondo State, Nigeria. - Okosun, S. E.; Omodehin, A. O.; Ajayi, I. S. (Advances in Social Sciences Research Journal, 2021)
Management of wastes which is a part of the daily activities of man is an important aspect of environmental management. Over the years, there have been concerted efforts made towards adequately solving the problems created by improper waste management and disposal in Nigeria cities. This study, appraises environmental management in cities; a perspective from the Ondo state Waste Management Authority (OSWMA) Akure. The broad objectives of this study are to identify types of wastes managed by OSWMA, describe the attitude and role of residents (household) toward solid waste management, and examine the possible constraints faced by OSWMA, Akure in the discharge of their duties. Samples were drawn from the total number of OSWMA staff and clients served by the authority in the core, transition and peripheral districts of Akure. 53 questionnaires were administered to the staff representing 10% of the total number of staff while 324 questionnaires representing 1% of residents were administered, collated and analyzed using SPSS version 19. The results of the analysis, revealed that majority (81.1%) of the staff respondents opined that the type of waste managed by the Authority is solid waste; using the door to door method of solid waste collection as submitted by 54.5% of the staff. On the other hand, majority of the households’ respondents (81.4%) expressed willingness to pay for service rendered by the authority. Findings also revealed that poor funding was the main constraints faced by the authority. The study therefore recommends proper funding, provision of equipment and facilities needed for smooth running of the authority in order to ensure effective collection and management of waste in the study area.